Enhancing the role of “Soft Power” in Promoting Azerbaijani Realities through “Azerbaijani State Diaspora” Organization - Ibrahimova, Dilara; Zadayeva, Nargiz; Mammadov, Rauf (ADA University, 2025)
The aim of this study is to analyze the potential of the Azerbaijani diaspora as a soft power instrument within the contemporary international system. Despite Azerbaijan’s ongoing involvement in numerous global initiatives, its soft power strategy remains limited due to institutional fragmentation, dispersed budget priorities, and the continued reliance on outdated programs. Grounded in Joseph Nye’s theoretical model of soft power, this research employs qualitative methods—including semi-structured expert interviews and comparative analysis of relevant international practices—to identify systemic shortcomings and formulate actionable policy solutions. The proposed alternatives focus on strategic institutional reforms, financial innovation, and modernization of diaspora engagement mechanisms to enhance Azerbaijan’s global influence
Keywords: Azerbaijani diaspora -- Political aspects; Diaspora engagement -- Azerbaijan; Foreign relations -- Public diplomacy -- Azerbaijan; International relations -- Citizen participation; National identity -- Political aspects -- Azerbaijan; Public and International Affairs